Stopping to Listen: Using Qualitative Methods to Inform a Web-Based Platform for Adults With Neurofibromatosis. (November 2021) - Lester, Ethan G.; Popok, Paula J.; Grunberg, Victoria A.; Baez, Alejandro; Herrawi, Farahdeba; Vranceanu, Ana-Maria
Introduction : Psychosocial care for people with neurofibromatosis (NF) is challenging to access. Therefore, we sought to develop a self-guided web-based treatment platform for people with NF based on the live video relaxation response resiliency program for NF (3RP-NF). Here we report on qualitative interviews with adult patients who participated in the 3RP-NF to: (a) understand participant perceptions of the 3RP-NF program and (b) gather feedback for a self-guided web-based treatment platform (i.e., NF-Web ).Methods : We conducted individual semistructured interviews ( N  = 23; videoconferencing). We utilized both the Framework method and a hybrid deductive and inductive approach to analyze qualitative data.Results : We examined findings within the following themes for both 3RP-NF and NF-Web: (a) general attitudes, (b) barriers and facilitators, and (c) program-specific factors. Participants endorsed positive attitudes towards the 3RP-NF and NF-Web and described unique barriers and facilitators to each and provided suggestions regarding technology, NF-specific needs, and ways to promote social support virtually.Conclusions : This study highlights the importance of gathering participant feedback when designing novel, illness-specific interventions. In future studies, we aim to provide people with NF effective and efficient access to psychosocial support that matches their needs and life context. Results are informing NF-Web development.